ANALISIS KESALAHAN BERBAHASA INDONESIA PADA TEKS NARASI SISWA KELAS XI SMA NEGERI 1 SUMBERLAWANG KABUPATEN SRAGEN - Ade Fian Bayu Aji Saputra; Atiqa Sabardila (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
The purpose of this paper is to describe the form of language errors in the narrative text of class XI students of SMA Negeri 1 Sumberlawang as Indonesian language learning. This analysis was conducted using a qualitative descriptive method. The source of the data obtained in this study came from the work of narrative texts by class XI students of SMA Negeri 1 Sumberlawang for the 2020/2021 academic year. Samples of narrative text work were taken from ten students of class XI from several different classes . The data in this study are in the form of words, phrases, clauses, and sentences contained in the narrative text of class XI students of SMA Negeri 1 Sumberlawang. The results of the analysis of narrative texts for class XI students of SMA Negeri 1 Sumberlawang, found that there were 4 error areas, namely (1) errors in the phonological field which included errors in the formation and changes of phonemes, (2) errors in the morphology field which included morpheme abbreviations and spelling errors, ( 3) errors in the field of syntax which include deviations in the structure of phrases, clauses or sentences, and (4) errors in the field of sociolinguistics which include mixing Indonesian with foreign languages ??in sentences. Keywords: Analysis, Language Error, Narrative Text